Water Stress Mitigation in the Vit River Basin Based on WEAP and MatLab Simulation - Emil Tsanov; Irina Ribarova; Galina Dimova; Plamen Ninov; Maggie Kossida; Christos Makropoulos (Salehan Institute of Higher Education, 2020)
The presented study aims at the development of an approach, which will enable selection of optimal measures for mitigation of water stress. The approach is based on two software pillars – Water Evaluation and Planning System (WEAP) and MatLab, which are applied in combination. The approach has three main steps: 1) modeling of the river basin with WEAP software 2) selecting mitigation measures and preparation of intervention curves and 3) running of an optimization using MatLab to select the mitigation measures. The set of the applied mitigation measures includes: reducing urban water demand and supply, reducing water demand for irrigation, and rehabilitation of the irrigation system. The result of the performed optimization with objectives set as minimal investment and water abstraction shows that in the Vit River basin the best combination of mitigation measures are a change in irrigation practice as well as reducing leakage in the irrigation distribution network and in the municipal distribution network. The optimization results show that 36% of the abstracted water could be saved if 2.1 million EUR were invested. The approach which was developed and applied in this work proved its suitability for facilitating decision making for water stress management at a river basin level. Doi: 10.28991/cej-2020-03091602 Full Text: PDF